2016
DOI: 10.1136/heartjnl-2015-309164
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular events and all-cause mortality with insulin versus glucagon-like peptide-1 analogue in type 2 diabetes

Abstract: In this cohort of obese people with T2DM, intensification of dual oral therapy by adding GLP-1ar analogue is associated with a lower MACE outcome in routine clinical practice, compared with adding insulin therapy as the third glucose-lowering agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(46 citation statements)
references
References 29 publications
1
45
0
Order By: Relevance
“…Previous studies also showed decreased mortality in patients taking metformin and increased mortality in patients taking sulfonylureas and insulin irrespectively of blood glucose control and duration of diabetes [10][11][12]. Improved ketogenesis can also be attributed to physical activity, type of diet, adenosine 5'-monophosphate-activated protein kinase (AMPK) activity and expression of the Foxa2 gene [13,14], although these factors were not analyzed in our study.…”
Section: Discussionmentioning
confidence: 73%
“…Previous studies also showed decreased mortality in patients taking metformin and increased mortality in patients taking sulfonylureas and insulin irrespectively of blood glucose control and duration of diabetes [10][11][12]. Improved ketogenesis can also be attributed to physical activity, type of diet, adenosine 5'-monophosphate-activated protein kinase (AMPK) activity and expression of the Foxa2 gene [13,14], although these factors were not analyzed in our study.…”
Section: Discussionmentioning
confidence: 73%
“…In populations of Asian origin, GLP‐1 RA may be of particular effectiveness because of the pathophysiological peculiarities of Asian type 2 diabetes and because of differences in body size and degree of obesity. Differences in baseline HbA1c probably do not explain much of the heterogeneity, since Buse et al (2015) found no difference in the HbA1c‐lowering capacity between GLP‐1 RAs and insulin regimens when analyzed by categories of baseline HbA1c. Furthermore, obvious differences between effects of short‐ and long‐acting GLP‐1 RAs probably contribute to overall heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…These study findings should be interpreted with caution, however, because the studies included a limited number of cardiovascular events and shorter follow‐up periods, the sulphonylureas used might also have had detrimental effects on cardiovascular disease (CVD), and the study populations were specific to either patients at an early stage of diabetes or those with existing CVD . Conversely, longitudinal cohort studies have shown an association between insulin therapy and increased risk of CVD and all‐cause mortality in patients with T2DM, but the effects of insulin therapy were only assessed in patients at an early stage of the antidiabetic treatment course, with insulin being used as monotherapy, or as second‐line or third‐line antidiabetic treatment …”
Section: Introductionmentioning
confidence: 95%